La ékphrasis en la tragedia griega (Minerva. Revista de Filología Clásica, 2019)
This article deals with a form of literary composition in Greek tragedy, that has been generally neglected. It begins with a review of the typologies under which the description is presented. The proportion of its presence in tire different parts of the drama is also investigated. It follows an analysis of a' number of significant specimina of ekphrasis, whereby their place and function in the general economy of the tragedies are taken into account.